Relay autotuning for identification and control - Chidambaram, M.; Sathe, Vivek (Cambridge : Cambridge University Press, 2014)
Proportional-integral-derivative (PID) controllers are extensively used for efficient industrial operations. Autotuning such controllers is required for efficient operation. There are two ways of relay autotuning cascade control systems - simultaneous tuning and sequential tuning. This book discusses incorporation of higher order harmonics of relay autotuning for a single loop controller and cascade control systems to get accurate values of controller ultimate gain. It provides a simple method of designing P/PI controllers for series and parallel cascade control schemes. The authors also focus on estimation of model parameters of unstable FOPTD systems, stable SOPTD and unstable SOPTDZ systems using a single relay feedback test. The methodology and final results explained in this book are useful in tuning controllers. The text would be of use to graduate students and researchers for further studies in this area.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Relay control systems; Self-tuning controllers; Electric relays -- Automatic control